How Meritocracy is Defined Today?: Contemporary Aspects of Meritocracy - Chang-Hee Kim; Yong-Beom Choi (Economics & Sociology)
This study aimed to develop a deeper understanding of contemporary aspects of meritocracy based on a qualitative meta-synthesis of the scholarly literature. Eighteen empirical studies of meritocracy in various disciplines were reviewed for this study. Thematic analysis revealed three main higher-order themes with six sub-themes that described the characteristics of meritocracy today. The findings present an overview of the current issues considered by meritocracy studies and provide a foundation for the ongoing debate over the necessary conditions for a better meritocracy.